Leadership in Public Administration: Prospects for Development in Ukraine - LIAKH, Yuliia (University Scientific Notes, 2022)
In modern conditions, Ukraine sets many tasks, based on the democratization of public administration. To a large extent, this applies to the development of leadership and methods of ensuring it as a universal lever through which the state influences the condition of social, economic and political development. Leadership as a stabilizing factor of public administration, integrates the interests of different groups of the population, plays an important role in their lives, activities, group decisions that are important for each member of such a group. Leadership development includes strategies, objectives and goals of public service activities that will help improve the quality of public administration. Aspects related to management activities can be developed on the basis of an institutional environment that provides a clear legal basis for the functioning of the public service; development of civil society and effective communication between government and citizens; organizes models of educational and scientific activities related to the acquisition of knowledge and competencies of public administration specialists and research on the development of leadership in public administration. It is noteworthy that a person who seeks public recognition and support from the general public must necessarily demonstrate a willingness to implement the socially expected constructs that function in the mass consciousness as a social ideal. However, the methods of achieving such designs can be radically different up to the choice of diametrically opposed and mutually exclusive directions. It turns out that the despotic form of political domination in most cases leads to the regression of civil society and the state as a whole. Methodologically, the approach to the development of knowledge, skills and competencies of public administration leaders should be based on democratic principles and educational approaches that will form civic and managerial knowledge (competencies), namely, the ability to solve complex problems in professional and innovative spheres with the potential of obtaining and forming new knowledge or practices; ability to identify and solve systemic problems of social significance in key areas of activity. Public sector leadership is a combination of skills and competencies that provide personal influence, goal setting, and strategic thinking. Leaders are the initiators of change and key figures in the success of democratic administrative reform. They formulate strategies and determine how to implement them. Defining the prospects for the development of leadership in public administration is currently very important and is seen as a key to improving the capacity of social governance, which will depend on the sustainable development of the whole country.
Keywords: leadership; leader; public administration; competencies